Acute Thyrotoxic Bulbar Myopathy with Encephalopathic Behaviour: An Uncommon Complication of Hyperthyroidism - Boddu, Neeraja J. (Hindawi Publishing Corporation, 2013)
Objective. Acute thyrotoxic bulbar palsy is rare, severe, and rapidly progressive. We describe a case of thyrotoxicosis with bulbar palsy, encephalopathy, and pyramidal tract dysfunction. Case Report. 64-year-old white male with toxic multinodular goiter presented with rapid atrial fibrillation. He had mild tremor, normal cranial nerve examination, 4/5 strength in all extremities, normal reflexes, and down going plantars. TSH was low at 0.09 (normal: 0.34–5.6 uIU/mL), and free T4 was high at 5.22 (normal: 0.47–1.41 ng/dL). Despite optimal AV nodal blockade, he had persistent rapid atrial fibrillation. He later developed cervical dystonia, rigidity, clonus, dysarthria, dysphagia, vocal cord palsy, and absent gag reflex. Thyroid storm was suspected. Neuroimaging and cerebrospinal fluid cultures were nondiagnostic. Acetylcholine receptor antibodies were negative. Swallow ability was impaired with heavy secretions. Remarkable improvement in symptoms was noted after initiation of treatment for thyroid storm. Conclusion. Pyramidal tract symptoms and bulbar palsy may occur with thyrotoxicosis. Cranial nerve involvement and encephalopathy raise a question of primary brain mechanism causing bulbar palsy. This is reversible with prompt treatment of thyroid storm.